Research on multi-source heterogeneous data fusion system based on device object model - Chen Yunqi (ITM Web of Conferences)
The effective fusion of data from multi-source heterogeneous automation subsystems in coal mines is a current industry problem. Problems such as inconsistent equipment models and inconvenient collection and configuration need to be solved urgently. Analyze the main electromechanical equipment and attribute information of the mine, establish a unified equipment object model, and develop equipment sensor monitoring data configuration systems for multiple protocols such as PLC, OPC, and TCP. It has functions such as online visualization configuration of equipment object attribute information, autonomous selection of collection protocols, and adaptive configuration of distributed parsing services. According to the on-site application table, the system has improved the efficiency of data fusion collection, reduced the difficulty of operation and maintenance, and accelerated the progress of intelligent mine construction, which has certain reference value.